How Students' Motıvatıonal Regulatıon Strategıes Influence Overall Engagement In Onlıne Learnıng - Sriwiyanti; Mohamad Yusoff, Siti Hajar; Saefudin, Wahyu (Jurnal Pembelajaran Inovatif, 2025)
Online learning has been researched extensively. However, prior studies found the challenges of online learning. Therefore, this study aims to observe the level of motivational regulation strategies and student engagement in online learning. It also examines the relationship and the influence of motivational regulation strategies on student engagement in online learning. This study applies a quantitative approach through a survey research design involving 411 university students in West Nusa Tenggara Province. Then, the data were analyzed using descriptive statistics, t-test, Pearson correlation, and regression analysis. The results indicate that most students had high motivational regulation strategies and moderate student engagement. Then, motivational regulation strategies significantly influence student engagement in online learning. This research can contribute to the education system, specifically to the Ministry of Education, in establishing methods to enhance the quality of learning. Besides, this research has implications for encouraging engagement and flourishing learning processes during online learning.